We'll Always Have Paris: The Definitive Guide to Great Lines from the Movies - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (HarperCollins Publishers, 1995)
Keywords: Motion pictures; Quotations, maxims, etc; dept.ils; dept.mat; faculty_collection

Nonnegativity results for generalized q-binomial coefficients - Fishel, S. (Discrete Mathematics, 1995)
Let q be a prime number. The number of subgroups of order qk in an abelian group G of order qn and type λ is a polynomial in q, [kλ′]q. In 1987, Lynne Butler showed that the first difference, [kλ′] - [k - 1λ′], has nonnegative coefficients as a polynomial in q, when 2k ≤ |λ|. We generalize the first difference to the rth difference, and give conditions for the nonnegativity of its coefficients. © 1995.
Keywords: dept.mat

Statistics for special q, t-kostka polynomials - Fishel, Susanna (Proceedings of the American Mathematical Society, 1995)
Kirillov and Reshetikhin introduced rigged configurations as a new way to calculate the entries of the Kostka matrix. Macdonald defined the two-parameter Kostka matrix whose entries generalize. We use rigged configurations and a formula of Stembridge to provide a combinatorial interpretation of in the case where is a partition with no more than two columns. In particular, we show that in this case, has nonnegative coefficients. © 1995 American Mathematical Society.
Keywords: dept.mat

Canonical bases for the Brauer centralizer algebra - Fishel, Susanna; Grojnowski, I (Mathematical Research Letters, 1995)
Keywords: dept.mat